2020
DOI: 10.1021/acs.inorgchem.9b03125
|View full text |Cite
|
Sign up to set email alerts
|

Metathesis Reactions between Heavy d-8 Fluorides and I(III)–Pyridine Complexes

Abstract: Between Heavy D8 Fluorides and I(III)-Pyridine Complexes. ChemRxiv. Preprint. The reaction between trans-[AuF2(pyridine)2]+ and [PhI(pyridine)2]2+ results in the formation of PhIF2 and [Au(pyridine)4]3+. Investigation of the reaction pathway using model Pd and Pt analogues of the gold complex indicate the most likely mechanism is attack by the Au-F onto the I(III), rather than a redox process. This demonstrates that the Au(III)-F fragment can behave in a nucleophilic manner even in a relatively electron poor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
(71 reference statements)
1
4
0
Order By: Relevance
“…We speculate that the target species bis-cyano bis-pyridyl complex was formed temporarily via ligand delivery from TMS, however this species then undergoes ligand exchange to produce the observed products. This scrambling behaviour has previously been observed with halides of Au(III).Recently we reported that the cationic difluorogold systems (6DMAP, 6IM) can undergo metathesis reactions with [PhI(pyridine)2] 2+ species via nucleophilic attack from fluoride onto the iodine resulting in transfer of pyridine to the gold and generation of PhIF2 27. To investigate if 6DMAP can also react with I(III) species bearing anionic ligands to give 12DMAP, which we were unable to synthesize oxidatively from Au(I), it was reacted with PhI(OAc)2 in CH3CN, resulting in a colour change from yellow to orange.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…We speculate that the target species bis-cyano bis-pyridyl complex was formed temporarily via ligand delivery from TMS, however this species then undergoes ligand exchange to produce the observed products. This scrambling behaviour has previously been observed with halides of Au(III).Recently we reported that the cationic difluorogold systems (6DMAP, 6IM) can undergo metathesis reactions with [PhI(pyridine)2] 2+ species via nucleophilic attack from fluoride onto the iodine resulting in transfer of pyridine to the gold and generation of PhIF2 27. To investigate if 6DMAP can also react with I(III) species bearing anionic ligands to give 12DMAP, which we were unable to synthesize oxidatively from Au(I), it was reacted with PhI(OAc)2 in CH3CN, resulting in a colour change from yellow to orange.…”
supporting
confidence: 66%
“…26 Recently we reported that the cationic difluorogold systems (6DMAP, 6IM) can undergo metathesis reactions with [PhI(pyridine)2] 2+ species via nucleophilic attack from fluoride onto the iodine resulting in transfer of pyridine to the gold and generation of PhIF2. 27 To investigate if 6DMAP can also react with I(III) species bearing anionic ligands to give 12DMAP, which we were unable to synthesize oxidatively from Au(I), it was reacted with PhI(OAc)2 in CH3CN, resulting in a colour change from yellow to orange. After two hours, the in situ 19 F NMR showed generation of PhIF2 as a singlet at -176 ppm.…”
Section: Reaction Of Au(iii) Difluorides With Phi(oac)2mentioning
confidence: 99%
“…34 Recently we reported that cationic difluorogold systems 6DMAP and 6IM can undergo metathesis reactions with [PhI(pyridine) 2 ] 2+ species via nucleophilic attack from fluoride onto the iodine, resulting in transfer of pyridine to the gold and generation of PhIF 2 . 35 To investigate if 6DMAP can also react with I(III) species bearing anionic ligands to give 12DMAP, which we were unable to synthesize oxidatively from Au(I), it was reacted with PhI(OAc) 2 in CH 3 CN, resulting in a color change from yellow to orange. After 2 h, in situ 19 F NMR showed the generation of PhIF 2 as a singlet at −176 ppm.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Riedel, Braun and co-workers reported the dissolution of gold metal in BrF 254,255 The addition of SIMes to either NMe 4 [AuF 4 ] at −30 °C or to AuF 3 at −80 °C to room temperature affords the carbene complex AuF 3 (SIMes) 89, which was characterized by X-ray diffraction. The 13 C NMR signal of the carbene-carbon in 89 is observed at δ 152.4 ppm, shifted upfield by ca.…”
Section: Trans-effect/trans-influencementioning
confidence: 99%
“…The analogous complexes with methylimidazole as donor ligands were also obtained and structurally characterized. [AuF 2 (py) 2 ] + undergoes pyridine/fluoride exchange with [PhI­(py) 2 ] 2+ to give [Au­(py) 4 ] 3+ and PhIF 2 . , …”
Section: General Aspects Of Gold(iii) Coordination Chemistrymentioning
confidence: 99%